Measuring income redistribution: Beyond the proportionality standard - Ivica Urban (University of Essex, Institute for Social and Economic Research (ISER), 2017)
Traditional analyses of redistributive effects of the tax-benefit system are rooted in the concepts of relative income inequality and proportionality. This observation also applies to decompositions proposed by Kakwani (1977, 1984) and Lambert (1985) that reveal the vertical and horizontal effects of tax-benefit instruments. This paper generalises those decompositions within the frameworks of the alternative inequality concepts suggested by Ebert (2004) and Bosmans et al. (2014). As expected, the results of the empirical analysis indicate that for different views of inequality, different taxes and benefits play significantly different roles in reducing inequality.
Keywords: D63; H22; H23; 330; inequality concepts; redistributive effect; vertical equity; taxes and benefits